Perancangan Desain Karakter untuk Buku Ilustrasi Interaktif tentang Karawitan Jawatimuran - Rifqi, Tifani Jihaniar; Romadhona, Mahimma; Masnuna, Masnuna (Innovative: Journal Of Social Science Research, 2024)
The decline in interest in Jawatimuran karawitan among younger generations, especially children, is influenced by several factors, such as globalization, limited exposure to this art form in formal education, and the lack of suitable learning media. To address this issue, there is a need for appropriate media, one of which is an interactive illustrated book designed to introduce and preserve karawitan for children aged 7-12 years. This study aims to design characters for this interactive illustrated book. Using a descriptive qualitative approach, data were collected through questionnaires, interviews, observations, and Focus Group Discussions (FGD) with children. The results indicate that visually appealing and emotionally relevant character designs can increase children's interest. The characters Raka, Faqih, Rania, and Pak Joko, designed with attention to local cultural values, are expected to serve as effective media to foster children's appreciation and pride in Jawatimuran karawitan.